X/3-(x-2)/2=7/3x

Simple and best practice solution for X/3-(x-2)/2=7/3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X/3-(x-2)/2=7/3x equation:



X/3-(X-2)/2=7/3X
We move all terms to the left:
X/3-(X-2)/2-(7/3X)=0
Domain of the equation: 3X)!=0
X!=0/1
X!=0
X∈R
We add all the numbers together, and all the variables
X/3-(X-2)/2-(+7/3X)=0
We get rid of parentheses
X/3-(X-2)/2-7/3X=0
We calculate fractions
There is no solution for this equation

See similar equations:

| 5×+8=2x-10 | | E^(2x+3)=37 | | 6n-5=-8n+13 | | -47y=-141 | | 6n-5=8n+13 | | (3x-10)-2x=15 | | 4x÷7=23 | | (4+g)(-11=121 | | 14-7x/10=8 | | (x-10)^2=784 | | 2-x+5/3=2x-4/4-x | | 2x^2-5x+8=23 | | -3y-(7)=2 | | 5x(3x-1)=120 | | 5√x-9=2 | | x2^2+9=18 | | 5x(5x-1)=120 | | 3x6+7=28 | | 6x/7+3=17 | | (x2)^2+9=18 | | 2x-10+x=10-x+8 | | 2x-x=21+3(2x+1) | | 5x+342=-4 | | 4y+1=2y=8 | | Y=0.2x-5.4 | | 3÷x+1=5÷2x | | n=–3+(n–1)(–2.2) | | 7/x=17.5/5 | | -19=-29-5y | | z2-0.667z+0.333=0 | | 7n^2+18n+8=0 | | 1=1.08x |

Equations solver categories